2019
DOI: 10.11591/ijece.v9i5.pp3375-3383
|View full text |Cite
|
Sign up to set email alerts
|

Performance of grid-connected solar photovoltaic power plants in the Middle East and North Africa

Abstract: A conceptual design Study of a solar electrical power system using PV array for a 5.3MW as nominal power required is presented. A Bird model has been used to estimate hourly, daily, monthly and yearly solar radiation amounts. f-f-chart is a design method was chosen to simulate the fraction of the solar energy required for the load given the PV array areas and climatic conditions. Four cities in the Middle East and North Africa representing different locations at southern Mediterranean region are selected Tripo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The energy equation is derived from Newton's first law, which states that the rate of change of energy inside a fluid element is equal to the rate of heat added to the fluid element and the work done on the fluid element. The energy equation used in this study can be written as formulated in Equation (8).…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The energy equation is derived from Newton's first law, which states that the rate of change of energy inside a fluid element is equal to the rate of heat added to the fluid element and the work done on the fluid element. The energy equation used in this study can be written as formulated in Equation (8).…”
Section: Simulation Methodologymentioning
confidence: 99%
“…These mostly fall within the ultraviolet spectrum. The optimal operating temperature for achieving maximum panel efficiency (also known as the standard test condition) is 25 • C [8]. This decreases by 0.25-0.5% for every 1 • C increase in temperature [9].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical output of the PV module under real operating conditions differs from Standard Test Conditions (STC), generally measured at 25 ⁰C and 1000 W/m 2 . Based on the temperature dependence of the opencircuit voltage, a reduction in the power conversion efficiency by 0.2-0.5% is observed with an increment of 1 °C [37]. The increase in module temperature causes a linear reduction of the output power [43][44][45].…”
Section: Performance Parametersmentioning
confidence: 98%
“…The understanding of the above-mentioned state-of-the-art cooling techniques is crucial to improve the efficiency of electrical output. Several researchers have conducted extensive reviews on various cooling methodologies, but to the best of our knowledge, there is limited review focusing only on passive cooling approaches [37,38]. Setting it apart from the aforementioned papers, the focus of this paper is to review the passive cooling methods for PV module that have been reported in the literature over the past two years.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the succeeding PCMs have been studied, such as: P.C.M [29-36], passive laminar flow heat sink [37][38][39][40][41][42] and radiant cooling [43][44][45][46].Understanding the advanced cooling techniques mentioned above is critical to improving electrical performance efficiency. Numerous researchers have showed in-depth analyses of different cooling methods attentions only on passive cooling approaches [47,48].…”
Section: Introductionmentioning
confidence: 99%